The Aesthetics of Place in Poetry Addressed to Children: A Reading of the Collection “Nagham ‘ala Nagham” by the Poet Qahtan Bayraqdar. - koussa, allaoua (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:9254b909-dbdd-43a2-a5ea-f2ea459c0796-1" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="de1c24a8-e2ef-4fd5-86f7-ab5ce23a54b7" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> In this article, we explore one of the most important components of the poetic text and a fundamental pillar in the aesthetics of poetic communication addressed to children, namely the “aesthetics of place.” This is approached through the poetry collection “Nagham ‘ala Nagham” by the poet Qahtan Bayraqdar, which won the Sharjah Award for Children’s Literature in 2008. The collection comprises thirty-one poetic texts that vary in their themes, purposes, and artistic and rhythmic structures. We begin with a theoretical framework in which we address the concept of place in both Arab and Western critical traditions, including its types, classifications, and connotations, as well as the importance of engaging with it in poetic corpora in general, and in poetry directed to children in particular. We then move on to applied examples through which we examine the poetics of place as manifested in the collection “Nagham ‘ala Nagham” intended for children.